Validation of relationships between tractor performance indicators, engine control unit data and field dimensions during tillage. (15th May 2023) - Janulevičius, Algirdas; Damanauskas, Vidas
Highlights: Engine control unit data processing for tractor performance analysis. Time efficiency was related to the average field length and width at widest point. Experimental ploughing time efficiency was determined from engine control unit data. Tractor performance was found to correlate with time efficiency in a linear relationship. A numerical dependence was found between engine control data and field dimensions. Abstract: In order to improve the efficiency of tillage and reduce the impact of the tractor on the environment, it is important to scientifically understand the relationship between the dimensions of the cultivated field and the operational indicators of the tractor. The purpose of this study is to find a numerical relationship between tractor tillage performance indicators (tractor working time efficiency, work efficiency, fuel consumption, engine power utilization), engine control unit data and field dimensions. A numerical relationship between field dimensions, tractor performance and engine control unit data were obtained by combining two methods to calculate tractor time efficiency. The first method was to calculate the time efficiency value of the tractor using the "load profile" data from the engine control unit. In the second method, the time efficiency value of the tractor was calculated from the average working speed, the working width of the implement, the field area, its average length and width at the widest point. It was found that the performance of the tractor when working in the soil correlates quite well with the time efficiency according to the linear dependence and with the average length of the field according to the exponential dependence.